2022
DOI: 10.1182/blood.2021012231
|View full text |Cite
|
Sign up to set email alerts
|

The megakaryocytic transcription factor ARID3A suppresses leukemia pathogenesis

Abstract: Given the plasticity of hematopoietic stem/progenitor cells, multiple routes of differentiation must be blocked during acute myeloid leukemia pathogenesis - the molecular basis of which is incompletely understood. Here we report that post-transcriptional repression of the transcription factor ARID3A by miR-125b is a key event in megakaryoblastic leukemia (AMKL) pathogenesis. AMKL is frequently associated with trisomy 21 and GATA1 mutations (GATA1s), and children with Down syndrome are at a high risk of develop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 81 publications
(100 reference statements)
1
25
0
Order By: Relevance
“…Comparative transcriptomic analysis of RNA-sequencing (RNA-seq) data substantiated the synergy between Gata1s mutations and RUNX1A expression. As previously described, gene set enrichment analysis (GSEA) revealed a marked reduction of erythroid genes and concurrent activation of pro-proliferative genes -including MYC and E2F targets -in Gata1s mutated FLCs (Figure 3C-D and Table S3) (Alejo-Valle et al, 2021;Klusmann et al, 2010;Ling et al, 2019). While RUNX1A expression mitigated the reduction of erythroid genes caused by Gata1s, it triggered a similar upregulation of MYC and E2F target genes, suggesting convergence on these oncogenic pathways.…”
Section: Runx1a Synergizes With Gata1s In the Leukemic Transformation...supporting
confidence: 63%
See 2 more Smart Citations
“…Comparative transcriptomic analysis of RNA-sequencing (RNA-seq) data substantiated the synergy between Gata1s mutations and RUNX1A expression. As previously described, gene set enrichment analysis (GSEA) revealed a marked reduction of erythroid genes and concurrent activation of pro-proliferative genes -including MYC and E2F targets -in Gata1s mutated FLCs (Figure 3C-D and Table S3) (Alejo-Valle et al, 2021;Klusmann et al, 2010;Ling et al, 2019). While RUNX1A expression mitigated the reduction of erythroid genes caused by Gata1s, it triggered a similar upregulation of MYC and E2F target genes, suggesting convergence on these oncogenic pathways.…”
Section: Runx1a Synergizes With Gata1s In the Leukemic Transformation...supporting
confidence: 63%
“…Importantly, Cre recombinase-mediated excision of the LoxP-flanked RUNX1A cDNA induced rapid depletion of the leukemic blasts in vitro , underlining their dependency on RUNX1A and its importance in ML-DS pathogenesis ( Figure S3H ). Of note, miR-125 further accelerated the leukemic transformation of Gata1s -FLCs by RUNX1A, suggesting synergy between RUNX1A and another well characterized oncogene on chromosome 21 (Alejo-Valle et al ., 2021; Emmrich et al, 2014) ( Figure S3I ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others found discrepancies in protein versus transcript levels during human erythropoiesis, particularly for GATA1 (13), and we found that ARID3a transcripts do not always correlate with protein levels in mature hematopoietic cell subsets (14). Recently, coimmunoprecipitation liquid chromatographymass spectrometry data, using the megakaryoblastic cell line CMK, revealed that both ARID3a and GATA1 acted in concert for proper regulation of megakaryopoiesis (9), but it is unclear if ARID3a is required for early erythropoiesis in human cells. Therefore, it is critical to assess requirements for individual TFs at the protein level during hematopoietic events.…”
Section: Introductionmentioning
confidence: 61%
“…ENCODE data of K562 cells showed considerable overlap between GATA1, GATA2, and ARID3a binding sites in many genes important for erythropoiesis, suggesting ARID3a may function with those factors, either as a TF or as an epigenetic regulator mediating opening/closing of chromatin in enhancer/promoter regions. Knockdown of ARID3a with shRNA in GATA1-mutated cells revealed a block in both megakaryocytic and erythroid differentiation and revealed 65% of predicted ARID3a binding sites in K562 cells overlap with GATA1 sites (9). Indeed, the globin locus and other differentially regulated genes exhibit close proximity of binding sites for ARID3a, GATA1, GATA2, and TAL1 (Fig.…”
Section: Discussionmentioning
confidence: 92%